2018
DOI: 10.1002/adom.201801189
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Loss‐Compensated Plasmonic Device

Abstract: in them are essential to explore the plasmonic behavior at various interfaces. Dielectric can be as inorganic and organic; its selection depends on their attributes. Presently organic materials are particularly attractive due to their long exciton lifetime which makes strong modal coupling in interaction with SPP probable. [4] To achieve strong coupling, organic material ought to possess limited transition linewidth [5] like using J-aggregate molecules at plasmonic interfaces. [6] But J-aggregate molecules req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…4 Since then, a strong coupling regime has been achieved through interactions among a variety of plasmonic structures and organic molecules 5−12 and has been widely applied in many fields, such as sensing, 13,14 surface-enhanced Raman scattering 15,16 and nanolasing. 17,18 Several studies have clearly demonstrated that the Rabi splitting energy is positively proportional to N V / where N is the molecular quantity and V is the dimension of vacuum field in hybrid systems. 19,20 Another fancy phenomenon induced by the plasmonic structure is extraordinary optical transmission (EOT), which makes the transmission efficiency above the conventional unit one based on the surface of a periodically patterned metal film, first reported by Ebbesen et al in 1998.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Since then, a strong coupling regime has been achieved through interactions among a variety of plasmonic structures and organic molecules 5−12 and has been widely applied in many fields, such as sensing, 13,14 surface-enhanced Raman scattering 15,16 and nanolasing. 17,18 Several studies have clearly demonstrated that the Rabi splitting energy is positively proportional to N V / where N is the molecular quantity and V is the dimension of vacuum field in hybrid systems. 19,20 Another fancy phenomenon induced by the plasmonic structure is extraordinary optical transmission (EOT), which makes the transmission efficiency above the conventional unit one based on the surface of a periodically patterned metal film, first reported by Ebbesen et al in 1998.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2004, Bellessa et al first achieved a strong coupling regime between SPPs and organic molecules at room temperature . Since then, a strong coupling regime has been achieved through interactions among a variety of plasmonic structures and organic molecules and has been widely applied in many fields, such as sensing, , surface-enhanced Raman scattering , and nanolasing. , Several studies have clearly demonstrated that the Rabi splitting energy is positively proportional to where N is the molecular quantity and V is the dimension of vacuum field in hybrid systems. , …”
Section: Introductionmentioning
confidence: 99%